WASTEWATER TREATMENTS: A REVIEW - Duha Zeki Al-Swefee; Malath I. Yousif; Fatimah Sahib Abed; Athraa Abdulamir Abdulrab (Scholar Express Journals, 2022)
Many water supplies are now contaminated by anthropogenic sources such as domestic and agricultural waste, as well as manufacturing activities, the public's concern about the environmental effects of wastewater contamination has grown. Several traditional wastewater treatment methods, such as chemical coagulation, adsorption, and activated sludge, have been used to eliminate pollution; however, there are several drawbacks, most notably high operating costs, because of its low operating and repair costs, the usage of aerobic waste water treatment as a reductive medium is gaining popularity. Furthermore, it is simple to produce and has a high efficacy and potential to degrade pollutants
Keywords: Sewage; Treatments; Physical treatment; Chemical treatment